Predictability of the Atlantic overturning circulation and associated surface patterns in two CCSM3 climate change ensemble experiments - Teng, Haiyan (author); Branstator, Grant (author); Meehl, Gerald (author) (Journal of Climate, 2011)
Predictability of the Atlantic Meridional Overturning Circulation (AMOC) and associated oceanic and atmospheric fields on decadal time scales in Community Climate System Model version 3 (CCSM3) at T42 resolution is quantified with a 700-year control run and two 40-member "perfect model" climate change experiments. After taking into account both the mean and spread about the mean of the forecast distributions, and allowing for the possibility of time evolving modes, the natural variability of the AMOC is found predictable for about a decade; beyond that range the forced predictability resulting from greenhouse gas forcing becomes dominant. The upper-500m temperature in the North Atlantic is even more predictable than the AMOC by several years. This predictability is associated with subsurface and sea surface temperature (SST) anomalies that propagate in an anticlockwise direction along the subpolar gyre and which tend to be prominent during the 10 years following peaks in the amplitude of AMOC anomalies. Predictability in the North Atlantic SST mainly resides in the ensemble mean signals after 3-4 forecast years. Analysis suggests that in CCSM3 the subpolar gyre SST anomalies associated with the AMOC variability can influence the atmosphere and produce surface climate predictability that goes beyond the ENSO time scale. However, the resulting initial-value predictability in the atmosphere is very weak.